A new species of Ambrysus Stål from west-central Mexico and new records for Ambrysus dyticus La Rivers in Central America (Heteroptera: Nepomorpha: Naucoridae) - Reynoso-Velasco, Daniel (Zootaxa, 2023)
The new species Ambrysus inecol Reynoso n. sp. from Mexico, which belongs to Section 3 of the Ambrysus signoreti Stål complex, is herein described and illustrated. This brings the total number of described species in the genus to 69, of which 61 belong to the nominal subgenus and 25 to the A. signoreti complex. Also, new country and department/state records are reported for the Central American A. dyticus La Rivers.